Implikasi Penggunaan Metode Akuntansi Hijau dalam Praktik Bisnis: Tinjauan Terhadap Keberlanjutan Lingkungan dan Kinerja Keuangan Perusahaan - Aria Aji Pratama; Eva Yuliana; Hera Nisalia; Kholifah Lestari; Zakia Al Idrus (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The study delves into the significance of green accounting methods within the framework of environmental sustainability and financial performance of companies across diverse sectors. Its aim is to gain a deeper understanding of the impact of implementing these methods on the correlation between sustainable business practices and financial performance of companies. With a focus on integrating green accounting into business strategies, this research explores its implications on profitability, liquidity, and organizational growth. The research methodology adopted employs a qualitative approach through meticulous analysis of literature. The steps encompass identifying the appropriate scope, selecting relevant data sources, conducting descriptive analyses, critically evaluating the authenticity of the literature used, and compiling and interpreting the findings. The research findings indicate that consistent use of green accounting has a positive impact on a company's financial performance. However, challenges related to established economic paradigms and the need for consistent definitions in the context of sustainable development remain obstacles. The amalgamation of social and environmental responsibilities in business decision-making holds significant potential for enhancing environmental management efficiency and financial performance of companies. Overall, green accounting practices promise a substantial influence in creating sustainable business models, demanding a shift in perspective and broader implementation.